2018
DOI: 10.3390/ijms19061672
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Is Necessary for Mitochondrial Function and Cell Health

Abstract: Vitamin D receptor (VDR) mediates many genomic and non-genomic effects of vitamin D. Recently, the mitochondrial effects of vitamin D have been characterized in many cell types. In this article, we investigated the importance of VDR not only in mitochondrial activity and integrity but also in cell health. The silencing of the receptor in different healthy, non-transformed, and cancer cells initially decreased cell growth and modulated the cell cycle. We demonstrated that, in silenced cells, the increased respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 52 publications
(60 reference statements)
2
117
0
Order By: Relevance
“…Also the two most important enzymes responsible for inactivation or activation of vitamin D (25OHD, CYP27B1 and CYP24A1), are located in the mitochondria, therefore damage to mitochondria may lead to impairment of vitamin D metabolism [29,30]. However, there is a study that confirmed vitamin D receptor is necessary for mitochondrial function and cell health [14]. Cubilin and megalin proteins have the key role for internalization of vitamin D into cells and interaction with nuclear and mitochondrial vitamin D receptors [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the two most important enzymes responsible for inactivation or activation of vitamin D (25OHD, CYP27B1 and CYP24A1), are located in the mitochondria, therefore damage to mitochondria may lead to impairment of vitamin D metabolism [29,30]. However, there is a study that confirmed vitamin D receptor is necessary for mitochondrial function and cell health [14]. Cubilin and megalin proteins have the key role for internalization of vitamin D into cells and interaction with nuclear and mitochondrial vitamin D receptors [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress as well myocardial injury as were ameliorated by calcitriol in rats [11]. In addition to, localization of VDR in the nuclear, recently they have been found in mitochondria of keratinocytes [12], megakaryocytes and platelets, where the translocation is mediated by the permeability transition pore activity [13,14]. Indeed, the function of VDR in mitochondria has been explained by some studies on several cell lines that they have proved that calcitriol suppresses mitochondrial respiration, as a gatekeeper of mitochondrial respiratory chain activity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using either VDR ablation or 1,25D 3 treatment approaches have made associations between VDR actions and mitochondrial respiratory activity along with production of intracellular ROS within several cell lines 42 . In all cell types it was found that upon VDR ablation there was an increase in respiration and ROS production associated with elevations in both mitochondrial COX2 and nuclear COX4I1 42 . On the other hand, 1,25D 3 treatment of skin keratinocytes resulted in decreased COX2 and COX4I1 mRNA levels, suggesting a concomitant reduction in intracellular ROS production 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using either VDR ablation or 1,25D3 treatment approaches have made associations between VDR actions and mitochondrial respiratory activity along with production of intracellular ROS within several cell lines 42 . In all cell types it was found that upon VDR ablation there was an increase in respiration and ROS production associated with elevations in both mitochondrial COX2 and nuclear COX4I1 42 . On the other hand, 1,25D3 treatment of skin keratinocytes resulted in decreased COX2 and COX4I1 mRNA levels, suggesting a concomitant reduction in intracellular ROS production 36 .…”
Section: Discussionmentioning
confidence: 99%